IMPROVING INVERTER OUTPUT CURRENT CONTROLLER UNDER UNBALANCED CONDITIONS BY USING VIRTUAL IMPEDANCE - Antonio Budiwicaksana, Lukas
Nowadays, three-phase inverters have been commonly used in power system, especially in renewable energy and motor drives application. In many applications, the inverter has to generate balanced sinusoidal three-phase current. In grid-tied inverter, usually the voltage grid is unbalanced. This unbalance produces unbalanced output currents of inverter. Unbalanced three-phase currents contain positive and negative sequence currents, that produces low frequency oscillation in DC side. The most common method to suppress this unbalance is the dual synchronous frame control method. This method is complicated due to the existence of sequence transformation block. This research proposes a novel method to balance the inverter output current under unbalanced ac side conditions. The proposed method is based on virtual impedance concept that is inserted in series to the inverter output. The proposed virtual impedance is an additional control algorithm that changes the inverter behavior into the one that has a real impedance connected on it. As it is virtual, the virtual impedance can be designed in such a way so that just the unbalanced signal is affected. Simulation and experimental results are included to show the effectiveness of the proposed method.